Tindak Tutur Ekspresif dalam Talkshow “Sarah Sechan” dan “The Ellen Degeneres Show”: Kajian Pragmatik Lintas Budaya - Ayu Wulandari (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
Language really helps human to express and share their life especially on media; language is becoming the tool to attract the listeners’ or audiences’ attention. This study focused on the use of expressive speech acts used by the talk show hosts of “Sarah Sechan” and “The Ellen DeGeneres Show” (two different hosts from Indonesia and from America). The research aimed to identify the similarity and the difference of expressive speech acts used by both hosts with the same topic through cross-cultural pragmatics point of view. The research used a qualitative descriptive method. The result showed that the host of Sarah Sechan talk show is considered friendlier due to the fact that the host used expressive speect acts and praised the guest more often than the host of The Ellen DeGeneres Show.